Antioxidant Activity From Water Extract Of Kecombrang Flower (Etlingera elatior) Leading To Jelly Candy Formulation - Dede Sukandar; Nani Radiastuti; Anna Muawanah; Adeng Hudaya (Syarif Hidayatullah State Islamic University, 2011)
A research on antioxidant activity of kecombrang flower ( Etlingera Elatior) water extract leading tojelly candy formulation was conducted. This experiment aims to elucidate the potential usage ofkecombrang flower as a functional food ingredient. Antioxidant activity of the kecombrang flowerwater extract was determined using Diphenyl Picryl Hidrazyl ( DPPH) method. In order to elucidatethe responsible compound for antioxidant activity, GCMS analysis was undertaken. Water extract ofkecombrang flower have antioxidant activity ( IC50=61,6497 ppm) and based on GCMS analysis itcontained 1-dodekanol ( tR=11,60, area=11,73, similarity at 95 %), 3-metil-1-oxo-2-buten 1-(21,41,51-trihidroxyl phenil) ( tR=13,02, area=3,17, similarity at 57 %) and 1-tetradecene ( tR= 13,26,area=6,03, similarity at 98 %). Formulation of jelly candy using kecombrang flower was designedand based on organoleptic test, C formula ( pink, sample code 763) was the optimum jelly pepermintformula with average score of 3,52.